Beginning server-side application development with Angular : discover how to rapidly prototype SEO-friendly web applications with Angular Universal - Borggreve, Bram (Packt Publishing, 2018)
Dynamic client-side web applications are great for UX, but not so much for your SEO. Learn how to build the same great UX with server-side Angular, all without taking a hit to search referrals.